Mesoporous NiCo2O4 nano-needles supported by 3D interconnected carbon network on Ni foam for electrochemical energy storage - Lu, Congxiang (2020)
In this work, a three dimensional (3D) interconnected carbon network consisting of ultrathin graphite (UG) and carbon nanotubes (CNTs) on Ni foam is fabricated and employed as a novel type of substrate for mesoporous NiCo 2 O 4 nano-needles. The successfully synthesized NiCo 2 O 4 nano-needles/CNTs/UG on Ni foam has many advantages including facile electrolyte access and direct conducting pathways towards current collectors, which enable it to be a promising electrode material in battery-like electrochemical energy storage. Encouragingly, a high capacity of 135.1 mAh/g at the current density of 1 A/g, superior rate performance and also stable cycling for 1200 cycles at the current density of 5 A/g have been demonstrated in this novel material.